Defining primary care and the chiropractic physicians' role in the evolving health care system - Kremer, Reiner G. (Elsevier, 2002)
OBJECTIVE: To review the literature assessing current trends within primary health care and its delivery and the role of the chiropractic primary care physician. DATA SOURCES: Select papers which offer definitions of primary care. DATA SYNTHESIS: Several influential papers offer criteria necessary to be considered primary care practitioners. RESULTS: Primary care is comprehensive, coordinated, continuous and accessible. Chiropractic care meets this definition. CONCLUSION: The primary care chiropractic physician is a viable and important part of the primary health care delivery system, with many chiropractic physicians currently prepared to participate effectively and competently in primary care.